2014
DOI: 10.1088/0031-9155/59/14/3893
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of a PRESAGE®in vivodosimeter for brachytherapy

Abstract: Determining accurate in-vivo dosimetry in brachytherapy treatment with high dose gradients is challenging. Here we introduce, investigate, and characterize a novel in-vivo dosimeter and readout technique with the potential to address this problem. A cylindrical (4 mm x 20 mm) tissue equivalent radiochromic dosimeter PRESAGE® In-Vivo (PRESAGE®-IV) is investigated. Two readout methods of the radiation induced change in optical density (OD) were investigated: (i) volume-averaged readout by spectrophotometer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The formulation of PRESAGE ® used in this study has Z eff of 7•6 and a physical density of 1•07 g/cm 3 . The physical dimensions of breast PRE-SAGE ® dosimeter were 13•8 cm (length) by 12•4 cm (width) and 4•6 cm (height) [15][16][17][18][19][20][21][22][23][24][25] as shown in Figure 2a. The dosimeter was scanned with the Duke midsized optical scanner dedicated for the RPC (DMOS-RPC) (Duke University, Durham, NC, USA) using 1°per step to produce 360 projection images.…”
Section: Savi™ Devicesmentioning
confidence: 99%
“…The formulation of PRESAGE ® used in this study has Z eff of 7•6 and a physical density of 1•07 g/cm 3 . The physical dimensions of breast PRE-SAGE ® dosimeter were 13•8 cm (length) by 12•4 cm (width) and 4•6 cm (height) [15][16][17][18][19][20][21][22][23][24][25] as shown in Figure 2a. The dosimeter was scanned with the Duke midsized optical scanner dedicated for the RPC (DMOS-RPC) (Duke University, Durham, NC, USA) using 1°per step to produce 360 projection images.…”
Section: Savi™ Devicesmentioning
confidence: 99%
“…Some dependence of the dose sensitivity on oxygen content in PRESAGE ® was also found [ 179 ]. Despite these unfavorable properties, the relative dose distribution was found to be reproducible within a 2% dose difference for an allowable distance-to-agreement of 2 mm [ 178 ], and PRESAGE ® was applied in some clinical dosimetric validation studies including IMRT [ 180 , 181 ], VMAT [ 182 , 183 ] in the determination of output factors of gamma knife radiosurgery [ 184 ] and in brachytherapy [ 185 , 186 , 187 ]. PRESAGE ® was also tested with hadron therapy, where a 20% dose underestimation was found in the Bragg peak for protons [ 188 ], but in another study with 400 MeV carbon ions, no significant LET effect on the dose response was observed [ 189 ].…”
Section: Radiochromic Gel Dosimetersmentioning
confidence: 99%
“…Meanwhile, the TLD has a deviation of 13.08%. In addition, PRESAGE also has a 98.9% agreement with the EBT2 film dose delivery in brachytherapy treatment [ 166 ]. Another study reported that PRESAGE provides an acceptable relative dose measurement for Ir-192 and Cs-137 brachytherapy sources [ 167 ].…”
Section: Dosimetry Applicationsmentioning
confidence: 99%